Ethical aspects in the management of antibacterial agents utilization - Renato Malta; Salvatore Di Rosa; Natale D’Alessandro (Italian Journal of Medicine, 2013)
Introduction: Antibacterial prescribing practices between 2004 and 2008 were investigated in the P. Giaccone University Hospital in Palermo, Italy to provide a foundation for critical analysis of the appropriateness of health-care resource usage. Materials and methods: Antibiotic prescribing practices between 2004 and 2008 were analyzed in the hospital as a whole and in different specialty areas. Results were expressed as defined daily doses (DDD) as a function of bed-days, number of admissions, and Diagnosis Related Group (DRG) points. Results: During the study period, increases were observed in the overall DDD per 100 bed-days (68.7 vs. 91.3) and the DDD per admission (4.53 vs. 5.54), but less variation was observed in the DDD/DRG score (3.55 vs. 3.63). Use of metronidazole, carbapenems, and glycopeptides increased, while use of third-generation cephalosporins, quinolones, and oral penicillins remained fairly stable. The drugs most commonly used in 2008 were (% of total DDD): levofloxacin (18.08%), amoxicillin + clavulanic acid (13.32%), ceftriaxone (9.01%), ciprofloxacin (8.21%), clarithromycin (5.74%), metronidazole (5.36%), ceftazidime (5.16%), amoxicillin (4.92%), gentamicin (1.88%), and meropenem (1.80%). An overall trend toward the prescription of newer wide-spectrum antibacterial agents was noted. National guidelines on chemoprophylaxis in surgery were observed in only 3/17 (17.7%) units. The prevalence of nosocomial infections was lower than those reported in the literature. Discussion: Although the cases treated in the hospital have become more complex over the years, the DDD documented in our study are far too high with respect to the actual clinical needs. These findings point to a trend toward the practice of excessively defensive medicine. Greater responsibility among physicians and the promotion of primary and secondary measures of preventive hygiene are fundamental to reduce the prescriptive pressure, a goal that should also have beneficial effects on health-care costs.